Association between Notch signaling pathway and cancer - Lachej, Nadežda; Didžiapetrienė, Janina; Kazbarienė, Birutė; Kanopienė, Daiva; Jonušienė, Violeta (Acta medica Lituanica, 2013)
Background. The components of the Notch signaling pathway are important in maintaining the balance involved in cell proliferation, apoptosis and differentiation. Therefore, dysfunction of the Notch prevents differentiation, ultimately guiding undifferentiated cells toward malignant transformation. The aim of this article is to present recently published data concerning the role of the Notch signaling pathway components in development and prognosis of oncologic diseases, in occurrence of resistance to cytostatic agents and importance in creating of new cancer treatment approaches. Materials and methods. The Pubmed was the main source of looking for information for this article. Results. Recent investigations show that disorders of the Notch signaling pathway are associated with development of some human haematological and solid cancers. In different tissues and organs this active pathway can act as a tumor suppressor or an oncogene. Accordingly, the increased or decreased expression of its components is defined. Most of published data show that the increased expression of Notch pathway components correlates with a worse prognosis of cancer and a shorter survival. Recently, the Notch pathway has been reported to be involved in drug resistance. The modulation of the Notch signaling pathway could be helpful in treatment of some tumors with abnormal activity of this pathway’s components. Therefore changes in the expression of Notch components could become important predictive factors, helpful in selecting the proper treatment method. Conclusions. The results of recent studies are very important, since the detecting of the prognostic and predictive value of components of the Notch signaling pathway can allow creating new and improving already known methods of cancer diagnostic and treatment.
Keywords: Notch signaling pathway; carcinogenesis; cancer